ANALISIS TRANSPORTASI DARAT TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN WAKATOBI - Matoka, Ulfa; Zain, Muhammad; Gunawan, Aldi; Sriningsih, Putri Ayu (JIM : Journal Of International Management, 2022)
The purpose of the study was to analyze the relationship  between land transportatioan and economic growth in Wakatobi Regency. This research is included in the type of quantitive research with the analytical method using multiple  linear regression, namely examining the vanable relationship between road length and number of motorized  vehicles with transportation economic growth in Wakatobi Regency. Result of the analysis the data shows (1) land transportation has a moderate level of linkages to ecomomic growth in Wakatobi Regency, (2) land transportation  has an effect of 23,3 percent on the ecomomis growth of transportation in Wakatobi Regency, (3) land transportation has no significant  effect on economic growth in Wakatobi Regency and (4) road length has a non-significant positive effect and the number of motorized vehicles has a negative effect on ecomomic growth in Wakatobi Regency.